3 - THE EFFECTS OF QUARANTINE ON HEALTHY LIFESTYLE HABITS IN MEXICO. (Fiep Bulletin - online, 2021)
Summary Introduction: The confinement that keeps families in their homes to combat the pandemic caused by COVID - 19, has caused children and adolescents to have considerably reduced the time that, in normal situations, they spent walking, running, enjoying any sport, playing in the schoolyard, on the street or in the park. An arrest that affects more than 125.9 million inhabitants in Mexico. On the other hand, prolonged periods of confinement can also have effects and consequences for mental and emotional health. The main objective of this research is to identify the state of health with respect to physical, nutritional and psychological activity of the Mexican population during quarantines that originate as a consequence of the COVID-19 virus epidemic. Methodology: Type of  descriptive and cross-sectional investigation; Where 300 subjects from different parts of the Mexican Republic participated (178 men and 122 women) between 20 and 50 years old, a survey was applied during the month of June 2020. Taking as main results that 75% of the Mexican population considers the importance of establishing a new routine, which adapts to different contexts, the physical space, the tasks to be performed and the organization of those with whom they live with. Concluding that the permanent practice of physical activity as far as possible, together with a healthy diet, is essential to maintain good health, physical and emotional well-being, in addition to prevent the development of non-communicable diseases, taking it as a fundamental element factor to better manage the effect of quarantine, helping to form healthy lifestyle habits.